MUTU LAYANAN PENDIDIKAN DI SDN 3 PERUMNAS WAY KANDIS KECAMATAN TANJUNG SENANG KOTA BANDAR LAMPUNG - Yessi Angguman; Sri Rahayu Ningsih (UNISAN JURNAL, 2024)
Elementary education plays an important role in shaping students’ character and basic knowledge, which will serve as the foundation for their further education. The quality of educational services in elementary schools significantly determines students’ success in achieving national education goals. At SDN 3 Perumnas Way Kandis, Tanjung Senang District, Bandar Lampung City, there is an urgent need to evaluate and improve the quality of educational services to ensure that all students receive a quality education. The problem statement in this study is to analyze and evaluate the quality of educational services at SDN 3 Perumnas Way Kandis, Tanjung Senang District, Bandar Lampung City. Evaluating the quality of educational services is important to ensure that the learning process runs effectively and efficiently, and meets established educational standards. This study aims to evaluate the quality of educational services at SDN 3 Perumnas Way Kandis, Tanjung Senang District, Bandar Lampung City. Evaluating the quality of educational services is important to ensure that the learning process runs effectively and efficiently, and meets established educational standards. This research uses a descriptive quantitative approach with a survey method. Data were collected through questionnaires distributed to students, teachers, and parents. The results of the study indicate that the quality of educational services at SDN 3 Perumnas Way Kandis is generally in the good category, with some aspects needing improvement, such as the availability of learning facilities, teacher training, and parental involvement in the educational process. Recommendations are provided for further improvements, including enhancing infrastructure, continuous training programs for teachers, and improving communication between the school and parents. These findings are expected to serve as a reference for the school and local education authorities in their efforts to improve the quality of educational services in the future.